RENTABILITAS USAHA PENJUALAN GABAH DI SUBAK DELOD SEMA DESA SADING KECAMATAN MENGWI KABUPATEN BADUNG - Karo, Monika; Arnawa, I Ketut; Martiningsih, Ni Gst. Ag. Gde Eka (Fakultas Pertanian dan Bisnis Universitas Mahasaraswati Denpasar, 2020)
The objectives of the study are: To determine the profitability of the expenditures of grain sales business groups in Subak Delod Sema, Sading Village, Mengwi District, Badung Regency and to determine the factors of grain selling Rentability in Subak Delod Sema Sading Village, Mengwi District, Badung Regency in December 2019 until February 2020. The location of this study was chosen by determining the location intentionally (Purposive) of 40 people employee ratio. The method used in this study is Rentability and Multiple Linear Regression Analysis The results of this study indicate that: The amount of profitability per month of grain sales business in Subak Delod Sema Sading Village in observing the last production cycle period (9th) is 4.41%, while Average Profitability per production cycle from observing 9 production cycles from 2017 - 2019 is 3.09%. Factors that influence Rentability are the number of processed unhusked rice (GKP) processed and operating profit while the sale value of gkg production does not have a statistically significant effect on Rentability.